The Echinococcus multilocularis cycle: first detection of intermediate host in a highly endemic region of Northeastern Italy - Salvatore Andrea Cafiero; Chiara Rossi; Lucia Cenni; Adriano Casulli; Heidi Christine Hauffe; Alessandro Massolo (Annals of Parasitology, 2024)
Echinococcus multilocularis (Em) is a Taeniidae cestode, distributed across the Northern hemisphere, and circulating among canids and voles as definitive and intermediate hosts, respectively (Romig et al., 2017. Adv. Parasitol. Part A, 95: 213-314). Humans can develop alveolar echinococcosis following egg ingestion (Conraths et al., 2017. PLOS NTD, 11: 1-15). In Italy, the first Em-positive foxes were found in the Trentino-Alto Adige region in an autochthonous and highly endemic focus (Manfredi et al., 2002. Vet. Rec., 150: 757; Casulli et al., 2005. Int J Par 35: 1079-1083; Obber et al., 2022. PLOS ONE, 17: e0268045). Recently,the first autochthonous case of alveolar echinococcosis was confirmed in the same area (Tamarozzi et al., 2024. Emerg. Infect. Dis., 30: 350-353). However, the role of rodents as intermediate hosts had never been investigated. We aimed to fill this knowledge gap in the region. Small mammals were collected from the stomachs of 148 legally culled foxes across the Province of Bolzano. For 142 prey items, species was identified from DNA extracted from tail or legs samples using PCR to amplify a 350 bp long fragment of cytb gene. A qPCR protocol was then used to screen for Em in liver and other organs for 98 rodents with QuantiNova Pathogen + IC Kit (Qiagen), following the manufacturer’s instructions with minor modifications, and Em-specific primers and probe targeting a 69 bp long fragment of cob gene (Massolo et al., 2021. Acta Trop., 223: 106078). Microtus arvalis (common vole) was the most frequent (20.83%) and abundant (116/142 individuals) prey species. Only 1/98 rodents was Em-positive: 1/38 M. arvalis livers. The infected vole was found in an Em-positive red fox near the border with Austria. We report the first finding of an Em-positive intermediate host in this endemic region which might help to explain why Em is distributed in the Southern Italian Alps. Phylogenetic analyses are planned soon.